(untitled) (Global Journal of Human-Social Science, 2017)
This study was conducted to examine the socioeconomic determinants of fuelwood usage by bread producers in Owerri North Local Government Area of Imo state. A total of 50 bread producers were sampled using simple random sampling technique. The data realized were analyzed using simple descriptive statistics and multiple regression models. Results shows 48 years as the mean age of the respondents and their household size were 5 persons while the number of years spent in formal schooling were 18 years among others. From the regression results, bakery experience in years (x=0.33, p